Analysis of genomic copy number variations through whole-genome scan in Chinese Qaidam cattle - Liu, Yangkai; Mu, Yanan; Wang, Wenxiang; Ahmed, Zulfiqar; Wei, Xudong; Lei, Chuzhao; Ma, Zhijie (Frontiers in Veterinary Science, 2023)
Qaidam cattle (CDM) are indigenous breed inhabiting Northwest China. In the present study, we newly sequenced 20 Qaidam cattle to investigate the copy number variants (CNVs) based on the ARS-UMD1.2 reference genome. We generated the CNV region (CNVR) datasets to explore the genomic CNV diversity and population stratification. The other four cattle breeds (Xizang cattle, XZ; Kazakh cattle, HSK; Mongolian cattle, MG; and Yanbian cattle, YB) from the regions of North China embracing 43 genomic sequences were collected and are distinguished from each of the other diverse populations by deletions and duplications. We also observed that the number of duplications was significantly more than deletions in the genome, which may be less harmful to gene formation and function. At the same time, only 1.15% of CNVRs overlapped with the exon region. Population differential CNVRs and functional annotations between the Qaidam cattle population and other cattle breeds revealed the functional genes related to immunity (MUC6), growth (ADAMTSL3), and adaptability (EBF2). Our analysis has provided numerous genomic characteristics of some Chinese cattle breeds, which are valuable as customized biological molecular markers in cattle breeding and production.